Narrative structure in the mind: Translating Genette's narrative discourse theory into a cognitive system. (December 2019) - Akimoto, Taisuke
Abstract: An episodic memory is considered to be mentally encoded or constructed information instead of a copy of the past events. However, the mechanism that constructs episodic memory has not been systematically formulated in previous studies on cognitive architecture and system. In this study, the term "story" is used, rather than episodic memory, to refer to a mental representation of temporally and linguistically organized events and entities. The main difference between a story and an episodic memory is that a story involves a form of mental representation, while the definition of an episodic memory is generally based on the function or content (i.e., it enables the recollection of past events). A story is considered as a uniform mental representation involving episodic memory, current situation, prospective memory, planned or imagined future, and fiction. To ensure systematic formulation of the story-form memory construction, this study introduces Genette's narrative discourse theory, which is a representative work in narratology. Genette provided a systematic classification of terms used to describe a narrative structure, with particular focus on how a narrative is structured on a text instead of what is told. In this study, Genette's narratological terms are analogically translated to methods of story-form memory construction in a cognitive system. Furthermore, the narratological methods are rearranged using cognitive terms including temporal segmentation of the world, generalization of stories, theory of mind, metacognition, self-formation, memory organization, and sociocultural aspect of cognition. Thus, a story is characterized as integrative, multifaceted, and multifunctional information in the mind.